Pengaruh Pajak Daerah, Retribusi Daerah, Dan Pendapatan Dari Laba Perusahaan Daerah Terhadap Belanja Modal Pada Kota Pekalongan Periode 2010-2019 - Alsya Ika Ameilia; Tsalis Syaifuddin (Jurusan Akuntansi Syariah Fakultas Ekonomi dan Bisnis Islam UIN K.H. Abdurrahman Wahid Pekalongan, 2022)
PAD is generated through local taxes, retribution, revenue of provicially owned corporation, and other legitimate local revenue. PAD revenue is varied, but the local government requires a large allocation of capital expenditures in order to increase the economic growth. The aims of this research are to know about interconnections between Local Taxes, Retribution, and Revenue of Provicially Owned Corporation to the Capital Expenditures in Pekalongan City during the years 2010-2019. This research is a quantitative with the technique of collecting data using documentation method. Data used comes from budget out comes years 2010-2019. The test of prerequisite analysis using classical assumption test. Then the hypothesis test using multiple linear regression analysis. The result showed that Local Taxes, Retribution, and Revenue of Provicially Owned Corporation have negative effect to the Capital Expenditures in Pekalongan City. However, simultaneously have positive effect to the Capital Expenditures in Pekalongan City. Keyword : Local Taxes, Retribution, Revenue of Provicially Owned Corporation, Capital Expenditures